Simulate cavitation bubble with single component multi-phase Lattice Boltzmann method - Xiong, Xin; Teschner, Tom-Robin; Moulitsas, Irene (Cranfield University, 2023)
Cavitation occurs when the pressure drops below a critical value at which point it can cause great damage to the machines such as propellers. In this study, a two-dimensional single bubble with different pressure differences between the boundary and the bubble will be studied based on the single component Shan-Chen model with the Carnahan-Starling (C-S) Equation of State (EOS) incorporated, which is similar to the model in [1-2]. Firstly, the model with the C-S EOS will be validated based on Maxwell’s equal area construction. The equilibrium density of liquid and vapor is obtained using a flat interface simulation according to [3]. It was demonstrated that the model has great thermal consistency according to this validation. Furthermore, we show results for a single bubble case for which its growth and collapse can be validated against the RayleighPlesset (R-P) equation with various pressure differences. Results show good agreement with the R-P equation and literature.
Keywords: Lattice Boltzmann Method (LBM); Cavitation; Single Bubble; Multiphase